The production of the rural landscape and its labour: The development of supply chain capitalism in the Swedish berry industry - Eriksson, Madeleine; Tollefsen, Aina (Bulletin of Geography. Socio-economic Series, 2018)
Increased commercial interest in wild berries in Northern Sweden's resource periphery has connected places and people to a global berry supply chain that produces goods for world markets. As a part of a wider global food chain, every link in this chain is deeply insecure and partly marked by secrecy and mystification. Contemporary representations of the Norrlandic landscape tend to obscure and hide economic conflicts and power relations connected to resource exploitation and corporate concentration, neglecting workers and local communities. This paper examines how globalization, neoliberal policies and the development of supply chain capitalism drive changes in labour markets and migration policies, which in turn shape/and are shaped by both material and immaterial aspects of the Norrlandic landscape. While many studies of global food chains have focused on abstract patterns of chain governance, business economics and logistics, we analyse the wild berry industry by centring on migrant workers and the production of a distinct spatiality through interconnectedness and historical conjuncture, with a starting point in a particular place in the interior of Norrland. We thereby contribute to a different narrative of the Norrlandic landscape, making visible power and labour relations.